Docência Universitária no estado do Piauí: concepções e dimensões didáticas do professor formado em pedagogia sobre sua prática pedagógica - Farias, Josélia Maria da Silva (2020)
In the face of the multiple transformations made in global scale in the social, political, economic, geographic and cultural fields, from the ongoing processes of the capitalist restructuring, globalization and neoliberalism, giving privilege to the market relations, the educational institutions had to redefine their roles over the new pattern of labor organization, of the labor’s profile as well as the types of formation. The study is bounded to the line of research “Saberes e Práticas Educativas”. The thesis argues that the pedagogical practice of the pedagogues who teach the subject Didactics in the public higher education institutions in Piaui corresponds to what the specialists in university teaching consider important as regards the conceptions of teaching and didactic dimensions. Therefore, the general purpose of this study is to investigate, study and comprehend which are the conceptions of teaching and didactic dimensions that the university professors, initially graduated in Pedagogy who work in Pedagogy courses and other degrees from public higher education institutions in the State of Piaui, have over their teaching practice in the higher education. It aims to display the interactions that these teachers establish among themselves and with the organization of their teaching work through the categories of study: conceptions of teaching and didactic dimensions. The research approaches a quantitative and qualitative methodology, in its priority is not only the data collection in its numeric form and percentage/ graphic and the opinion of the subjects in order to respond the following questions: 1 What are conceptions of teaching and didactic dimensions that the university professors, initially graduated in Pedagogy who work in Pedagogy courses in public higher education institutions in the State of Piaui, have over their teaching practice in the higher education? 2. What are the interactions that these teachers establish among themselves and with the organization of their teaching work through the categories of study: conceptions of teaching and didactic dimensions? Two Brazilian public universities that serve the whole state of Piaui, Universidade Federal Do Piaui (UFPI) – and in its 05 campuses, and the Universidade Estadual do Piaui (UESPI) – in its 11 campuses where there is the Pedagogy Course were chosen as research locations. were chosen as research locations. The used research instrument was a structured questionnaire developed in the Google Docs platform with closed questions disposed on a 5-point Likert-type scale and an opened one. We used the descriptive statistics to analyze the quantitative data and the analysis of the content by Bardin to analyze the qualitative ones. 40 professors who teach the Didactics subject in Pedagogy courses and other degrees in the public universities of the state of Piaui. The results allowed deducing that the pedagogue professors who teach the Didactics subject in Pedagogy courses and other degrees in the public universities of the state of Piaui, in their teaching practice in higher education, give privilege to a multidimensional perspective of education and teaching, therefore, think over the Didactics embedded to its epistemological principles, promoting critical reflections on the complexity about teaching, including, however, the analysis of the sociocultural, political, economic, technical, ethical, cognitive, human that interconnect in the construction/reconstruction of the knowledge historically constituted. Furthermore, in their teaching practice, they realize the teaching permeated by the contradictions and dilemmas in the contexts, in which they are inserted. Therefore, Didactics contributes to the professors exercise their educative actions in a transforming perspective of the factors that complicate the realization of a public, democratic and good education.